Pemodelan Realisasi Keuangan Menggunakan Maqasid Syariah di Kabupaten Bangka Tengah - Wijayanti, Riska (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
This study discusses how financial realization in data monitoring and evaluation of the regional budget for Central Bangka Regency is following the maqasid sharia approach or is still open. Also, this research will provide a new model for regional development programs following the 5 maqasid sharia priorities. This research uses a qualitative approach, Analytic Network Process or ANP, with case studies in the Central Bangka Regency area.This method is a way of obtaining decisions and using calculations to obtain ratios. The data from this study were obtained from interviews with related sections, direct observation, and related data. This research shows that the Realization of Monitoring and Evaluation of Data in Central Bangka Regency has not approached the 'maqasid asy-syarÿÿah' approach. Also, this study will find a new Data Monitoring and Evaluation model following the concept ofmaqasid sharia.